Synthesis and Anti-Inflammatory and Analgesic Potentials of Ethyl 2-(2,5-Dioxo-1-Phenylpyrrolidin-3-yl)-2-Methylpropanoate - Abdul Sadiq; Muhammad Arif Khan; Rehman Zafar; Farhat Ullah; Sajjad Ahmad; Muhammad Ayaz (MDPI AG, 2024)
Background/Objectives: Inflammation and analgesia are two prominent symptoms and often lead to chronic medical conditions. To control inflammation and analgesia, many marketed drugs are in practice but the majority of them have severe side effects. Methods: This study involved the synthesis of a pivalate-based Michael product and evaluated it for in vitro COX-1, COX-2, and 5-LOX inhibitory potentials using specific assays. Molecular docking studies were also assessed. Based on the in vitro results, the compound was also subjected to in vivo anti-inflammatory and antinociceptive studies. Results: The pivalate-based Michael product (MAK01) was synthesized by an organocatalytic asymmetric Michael addition of ethyl isobutyrate to N-phenylmaleimide with an isolated yield of 96%. The structure of the compound was confirmed through 1H and 13C NMR analyses. The observed IC50 values for COX-1, COX-2, and 5-LOX were 314, 130, and 105 μg/mL, respectively. The molecular docking studies on the synthesized compound showed binding interactions with the minimized pockets of the respective enzymes. In a carrageenan model, a percent reduction in edema when administered at 10 mg/kg (a reduction of 33.3 ± 0.77% at the second hour), 20 mg/kg (a reduction of 34.7 ± 0.74% at the second hour), and 30 mg/kg (a reduction of 40.58% ± 0.84% after the fifth hour) was observed. The compound showed a significant response at concentrations of 50, 100, and 150 mg/kg with latency times of 10.32 ± 0.82, 12.16 ± 0.51, and 12.93 ± 0.45 s, respectively. Conclusion: In this study, we synthesized a pivalate-based Michael product for the first time. Moreover, based on its rationality and potency, it was found to be an effective future medicine for the management of analgesia and inflammation.